Spontaneously Resolving Hyperreninemic Hypertension Caused by Accessory Renal Artery Stenosis in a 13‐Year‐Old Girl: A Case Report. Issue 1 (15th August 2016) - Akbeyaz, Ismail Hakki; Tirosh, Amit; Robinson, Cemre; Broadney, Miranda M.; Papadakis, Georgios Z.; Belyavskaya, Elena; Lyssikatos, Charalampos; Lodish, Maya B.; Stratakis, Constantine A.
Abstract : The authors describe the clinical investigation and progress of a 13‐year‐old girl diagnosed with hypertension 4 years prior to her admission. A thorough history was taken and physical examination performed. Laboratory analysis and relevant radiological evaluation were obtained in order to determine the etiology for suspected secondary hypertension, and later to differentiate between the possible causes of hyperreninemic hypertension. The patient had an accessory left renal artery, presumptively leading to renin secretion by the underperfused kidney. The patient was treated medically with spontaneous resolution of her hypertension and near normalization of plasma renin activity. On repeat imaging, the artery was not demonstrated. The authors concluded that the diagnosis of hyperreninemic hypertension in young ages should prompt investigation for the etiology. However, cautious observation is a valid option that might lead to spontaneous resolution.